Transcriptional silencing in Saccharomyces cerevisiae and Schizosaccharomyces pombe - Huang, Ying (Oxford University Press, 2002)
Transcriptional silencing is a heritable form of gene inactivation that involves the assembly of large regions of DNA into a specialized chromatin structure that inhibits transcription. This phenomenon is responsible for inhibiting transcription at silent mating-type loci, telomeres and rDNA repeats in both budding yeast Saccharomyces cerevisiae and fission yeast Schizosaccharomyces pombe, as well as at centromeres in fission yeast. Although transcriptional silencing in both S.cerevisiae and S.pombe involves modification of chromatin, no apparent amino acid sequence similarities have been reported between the proteins involved in establishment and maintenance of silent chromatin in these two distantly related yeasts. Silencing in S.cerevisiae is mediated by Sir2p-containing complexes, whereas silencing in S.pombe is mediated primarily by Swi6-containing complexes. The Swi6 complexes of S.pombe contain proteins closely related to their counterparts in higher eukaryotes, but have no apparent orthologs in S.cerevisiae. Silencing proteins from both yeasts are also actively involved in other chromosome-related nuclear functions, including DNA repair and the regulation of chromatin structure.